Alleviation of Liver Dysfunction, Oxidative Stress and Inflammation Underlies the Protective Effect of Ferulic Acid in Methotrexate-Induced Hepatotoxicity - Roghani M; Kalantari H; Khodayar MJ; Khorsandi L; Kalantar M; Goudarzi M; Kalantar H (Dove Medical Press, 2020)
Mozhdeh Roghani,1 Heibatullah Kalantari,1,2 Mohammad Javad Khodayar,1,2 Layasadat Khorsandi,3 Mojtaba Kalantar,4 Mehdi Goudarzi,5 Hadi Kalantar1,2 1Toxicology Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 2Department of Toxicology, Faculty of Pharmacy, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 3Cellular and Molecular Research Center, Department of Anatomical Sciences, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 4Student Research Committee, Shoushtar University of Medical Sciences, Shoushtar, Iran; 5Medicinal Plant Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, IranCorrespondence: Hadi KalantarDepartment of Toxicology, Faculty of Pharmacy and Toxicology Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, IranTel/Fax +98-613738378Email Kalantar-h@ajums.ac.irIntroduction: In multiple studies, involvement of oxidative stress in the pathogenesis of methotrexate (MTX)-mediated liver damage has been confirmed. Use of many drugs has been examined experimentally in order to prevent or diminish oxidative stress. However, no study has yet examined the effects of ferulic acid (FA) on MTX-induced liver damage. This study aimed at evaluating the effects of FA on protection against liver damage induced by MTX in mice.Materials and Methods: In this the mice were divided into five groups in a random manner: I) control; II) MTX (20 mg/kg); III and IV) FA (50 and 100 mg/kg) + MTX; and V) FA (100 mg/kg), and we measured serum factors, oxidative stress and inflammatory factors.Results: In the MTX group, accumulation of inflammatory cells, accumulation of red blood cell (RBC), and nuclear pyknosis (NP) were detected in the liver. In line with the histological data, the levels of nitric oxide (NO), malondialdehyde (MDA), interleukin-6 (IL-6), and tumor necrosis factor-α increased (TNF-α), whereas the reduced glutathione (GSH), catalase (CAT), total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione peroxidase (GPx) content reduced in the MTX group. However, FA ameliorated these hazardous effects in the antioxidant and anti-inflammatory systems in MTX-treated groups.Conclusion: Based on our findings, oxidative stress impairment and MTX-induced liver damage were ameliorated following FA pretreatment at both histological and biochemical levels. Therefore, FA can be effectively used in abrogation of MTX-induced toxicity.Keywords: methotrexate, oxidative damage, inflammation, ferulic acid, mice